2013
DOI: 10.1136/jech-2012-202265
|View full text |Cite
|
Sign up to set email alerts
|

Mortality differentials 1991−2005 by self-reported ethnicity: findings from the ONS Longitudinal Study

Abstract: Immigrants are selected for good health. This has offset the impact of socioeconomic disadvantage on the mortality of minority ethnic groups. As the immigrant population ages and the UK-born minority ethnic population grows, ethnic differentials in all-cause mortality are likely to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 28 publications
(22 reference statements)
6
36
1
Order By: Relevance
“…The study's most important result -a statistically significant (p<.01) excess mortality among second-generation North African-origin adult males -is based on only 22 deaths in the ELM. Even though this result is consistent with other European studies (Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017), our study calls for replication in the French context. However, we are not aware of any alternative source of mortality data in France with variables allowing the proper identification of second-generation immigrants.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study's most important result -a statistically significant (p<.01) excess mortality among second-generation North African-origin adult males -is based on only 22 deaths in the ELM. Even though this result is consistent with other European studies (Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017), our study calls for replication in the French context. However, we are not aware of any alternative source of mortality data in France with variables allowing the proper identification of second-generation immigrants.…”
Section: Discussionsupporting
confidence: 92%
“…In proportionate terms, second-generation immigrants represented 6.0% of the total EU population in 2014, up from 5.2% in 2008 (Agafiţei and Ivan 2017). Although research is sparse, second-generation status has been identified in previous studies as an important source of health disparities in EU countries, with important disadvantages in mortality outcomes for certain second-generation subgroups, especially those of non-EU origin (Harding and Balarajan 1996;Razum et al 1998;Tarnutzer, Bopp, and Grp 2012;Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017). Explanations for these mortality disadvantages include lower socioeconomic status, detrimental health behaviors, and chronic stress arising from perceived discrimination (Scott and Timaeus 2013;De Grande et al 2014;Manhica et al 2015;Vandenheede et al 2015;Wallace 2016;Jervelund et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] It is important to discuss the meaning of health inequalities while considering the socio-economic position and political factors that contribute to health services accessibility and cultural elements that influence the social representation of the healthdisease process. [6][7][8] The ethnic composition of industrialized nations differs from developing countries and the analysis of health inequalities requires consideration of the sociopolitical context of the countries; in some cases, changes in ethnic classification captures the emergence or redefines marginal groups.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are known to have an impact on morbidity and mortality (i.e., the material pathway) [7,8] and to contribute to ethnic inequalities in mortality [9,10]. In addition, the institutional arrangements and policies may be reciprocally linked to the host population’s attitudes towards immigrants [2,5,11], all of which might affect immigrants’ health through chronic negative daily stressors such as experiences of social exclusion, intolerance and discrimination (i.e., psychosocial pathway) [7,12].…”
Section: Introductionmentioning
confidence: 99%